Early events in spontaneous neutrophil apoptosis. (1st June 2004) - Scheel-Toellner, D.; Wang, K.-Q.; Webb, P.R.; Wong, S.H.; Craddock, R.; Assi, L.K.; Salmon, M.; Lord, J.M.
Abstract : Neutrophils are very abundant, short-lived leucocytes and their death by apoptosis is central to homoeostasis and the resolution of inflammation, yet the trigger for apoptosis is still a topic of debate. Depolarization of the mitochondrial membrane has been supposed to initiate neutrophil spontaneous apoptosis, as neutrophils gradually lose the anti-apoptotic protein Mcl-1 and Bax translocates and inserts into the mitochondrial membrane. However, other reports show that caspase 8 is required for neutrophil apoptosis, suggesting the involvement of DR (death receptor) signalling. As DR ligation is not required for neutrophil apoptosis, this raises the intriguing possibility that activation of caspase 8 during neutrophil apoptosis occurs via a novel mechanism. In the present paper, we discuss the current evidence for mechanisms occurring in neutrophil apoptosis, which could trigger DR signalling in the absence of DR ligation.